Influence of addition of silanized nanosilica and glycerol on hydrophobicity of starch using a factorial design - Lopes,Fernando Luis Panin (2017)
Abstract The thermoplastic starch (TPS) is regarded as a promising material for manufacturing packaging and products with biodegradable properties. This study aimed at obtaining hydrophobic starch using silanized silica nanoparticles (nSS) with hexamethyldisilazane. A factorial design 22 with central point was developed to evaluate the influence of glycerol (plasticizer) and nSS addition on the properties of water absorption, solubility and TPS contact angle. The materials morphology was also evaluated by means of scanning electron microscopy. The amount of glycerol and nSS influenced on starch hydrophobic character, for the increase of the glycerol dosage contributed to the increase of absorption and solubility of TPS in water. On the other hand, nSS has greater influence on the characteristics related to the TPS surface, favoring an increase of up to 27% in the contact angle values. Therefore, the sample with the greatest hydrophobic character was obtained by using lowest amounts of glycerol (30%) and highest amounts of nSS (5%).